Integration of miRNA:mRNA Co-Expression revealed crucial mechanisms modulated in immunogenic cancer cell death - Lamberti, María Julia (2022)
Immunogenic cell death (ICD) in cancer represents a functionally unique therapeutic response that can induce tumor-targeting immune responses. ICD is characterized by the exposure and release of numerous damage-associated molecular patterns (DAMPs), which confer adjuvanticity to dying cancer cells. The spatiotemporally defined emission of DAMPs during ICD has been well described, whereas the epigenetic mechanisms that regulate ICD hallmarks have not yet been deeply elucidated. Here, we aimed to examine the involvement of miRNAs and their putative targets using well-established in vitro models of ICD. To this end, B cell lymphoma (Mino) and breast cancer (MDA-MB-231) cell lines were exposed to two different ICD inducers, the combination of retinoic acid (RA) and interferon-alpha (IFN-α) and doxorubicin, and to non ICD inducers such as gamma irradiation. Then, miRNA and mRNA profiles were studied by next generation sequencing. Co-expression analysis identified 16 miRNAs differentially modulated in cells undergoing ICD. Integrated miRNA-mRNA functional analysis revealed candidate miRNAs, mRNAs, and modulated pathways associated with Immune System Process (GO Term). Specifically, ICD induced a distinctive transcriptional signature hallmarked by regulation of antigen presentation, a crucial step for proper activation of immune system antitumor response. Interestingly, the major histocompatibility complex class I (MHC-I) pathway was upregulated whereas class II (MHC-II) was downregulated. Analysis of MHC-II associated transcripts and HLA-DR surface expression confirmed inhibition of this pathway by ICD on lymphoma cells. miR-4284 and miR-212-3p were the strongest miRNAs upregulated by ICD associated with this event and miR-212-3p overexpression was able to downregulate surface expression of HLA-DR. It is well known that MHC-II expression on tumor cells facilitates the recruitment of CD4+ T cells. However, the interaction between tumor MHC-II and inhibitory coreceptors on tumor-associated lymphocytes could provide an immunosuppressive signal that directly represses effector cytotoxic activity. In this context, MHC-II downregulation by ICD could enhance antitumor immunity. Overall, we found that the miRNA profile was significantly altered during ICD. Several miRNAs are predicted to be involved in the regulation of MHC-I and II pathways, whose implication in ICD is demonstrated herein for the first time, which could eventually modulate tumor recognition and attack by the immune system.